Thoracic pain in patients with chronic interstitial lung disease—an underestimated symptom - Scherer, Manuela J.; Kampe, Sandra; Fredebeul-Beverungen, Jonas; Weinreich, Gerhard; Costabel, Ulrich; Bonella, Francesco (Frontiers in Medicine, 2023)
Introduction Prevalence and predisposing factors for the development of thoracic pain in patients with chronic interstitial lung disease are largely unknown. Underestimation and insufficient therapy of pain can lead to worsened ventilatory function. Quantitative sensory testing is an established tool for characterization of chronic pain and its neuropathic components. We investigated frequency and intensity of TP in cILD patients and the potential association with lung function and quality of life. Material and Methods We prospectively investigated patients with chronic interstitial lung disease to analyze risk factors for the development of thoracic pain and quantify thoracic pain through quantitative sensory testing. In addition, we studied the relationship between pain sensitivity and lung function impairment. Results 78 patients with chronic interstitial lung disease and 36 healthy controls were included. Thoracic pain occurred in 38 of 78 patients (49%), most frequently in 13 of 18 (72%, p=0.02) patients with pulmonary sarcoidosis. The occurrence was mostly spontaneous and not related to thoracic surgical interventions (76%, p=0.48). Patients with thoracic pain showed a significant impairment of mental well-being (p=0.004). A higher sensitivity to pinprick stimulation during QST can be observed in patients with thoracic pain (p<0.001). Steroid treatment was associated with lower sensitivity within thermal (p=0.034 and p=0.032) and pressure pain testing (p=0.046). We observed a significant correlation between total lung capacity and thermal (p=0.019 and p=0.03) or pressure pain sensitivity (p=0.006 and p=0.024). Conclusion This study was performed to investigate prevalence, risk factors and thoracic pain in patients with chronic interstitial lung disease. Thoracic pain mostly occurs spontaneous as a frequent symptom, and seems to be an underestimated symptom in patients with chronic interstitial lung disease, especially those with pulmonary sarcoidosis. Timely identification of thoracic pain may allow starting symptomatic treatment at early stage, before impairment in quality of life occurs.